Why don't families initiate treatment? A qualitative multicentre study investigating parents' reasons for declining paediatric weight management. Issue 4 (1st May 2015) - Perez, Arnaldo; Holt, Nicholas; Gokiert, Rebecca; Chanoine, Jean-Pierre; Legault, Laurent; Morrison, Katherine; Sharma, Arya; Ball, Geoff
Abstract: BACKGROUND: Many families referred to specialized health services for managing paediatric obesity do not initiate treatment; however, reasons for noninitiation are poorly understood. OBJECTIVE: To understand parents' reasons for declining tertiary-level health services for paediatric weight management. METHOD: Interviews were conducted with 18 parents of children (10 to 17 years of age; body mass index ≥85th percentile) who were referred for weight management, but did not initiate treatment at one of three Canadian multidisciplinary weight management clinics. A semi-structured interview guide was used to elicit parents' responses about reasons for noninitiation. Interviews were audio-recorded and transcribed verbatim. Data were managed using NVivo 9 (QSR International, Australia) and analyzed thematically. RESULTS: Most parents (mean age 44.1 years; range 34 to 55 years) were female (n=16 [89%]), obese (n=12 [66%]) and had a university degree (n=13 [71%]). Parents' reasons for not initiating health services were grouped into five themes: no perceived need for paediatric weight management (eg, perceived children did not have a weight or health problem); no perceived need for further actions (eg, perceived children already had a healthy lifestyle); no intention to initiate recommended care (eg, perceived clinical program was not efficacious); participation barriers (eg, children's lack of motivation); and situational factors (eg, weather). CONCLUSION: Physicians should not only discuss the need for and value of specialized care for managing paediatric obesity, but also explore parents' intention to initiate treatment and address reasons for noninitiation that are within their control.